The space and place of humans and humanity in language: Arabic and Indonesian compared - Muassomah,; Abdullah, Irwan; M. Faisol,; Toisuta, Hasbollah (Penerbit Universiti Kebangsaan Malaysia, 2020)
Language, aside from representing the culture of a people, also constructs humankind and humanity. Arabic conceptualizes humanity differently than the world's other languages, such as Indonesian. In Arabic, humans are positioned as subordinate, as dependent on God, whereas in Indonesian they are characterized as autonomous. This article seeks to analyse how language positions humans within their relationships with God, other humans, and nature. Arabic and Indonesian both incorporate implicit concepts of human being, godliness, and humanity, and thus these languages have broad space for defining humanity's relationship with God. This article concludes that Arabic positions humans as creatures whose values and attitudes are dependent on God, while Indonesian positions humans as autonomous and free creatures. The link between Arabic and religion and between Indonesian and culture has informed how these languages conceptualize and position humanity. This study recommends a comprehensive comparative investigation of how various languages position and understand humans and humanity.